Analysis of economic losses due to diseases in the buffalo production system in the department of Córdoba, Colombia (2021)
The objective of this work was to analyze the economic losses due to diseases in the buffalo production system in the department of Córdoba in Colombia. It was based on the information generated in the baseline, but with a treatment with greater specificity in the subject of diseases. The information originated from two sources: A survey on producers applied to 30 producers and a participatory workshop, using the multiple criteria analysis method through a consensus with producers. The data were organized in flat files, descriptive statistics and percentage calculations were calculated within the different categories of animals as well as the variables: production and mortality rates, decreased production due to disease. The results show that diseases related to hemoparasites and endoparasites incur a greater number of products for treatment, in the case of symptomatic charcoal, only preventive treatment consisting of the vaccine is done. In this context, it is concluded that the largest component of the cost is for medicines with 68% of the calculated total, followed by calf losses with 11% and finally meat production with 6%. In total the losses were estimated at 30235048 COP pesos.